1994
DOI: 10.1007/bf02103006
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic responses among battered women who kill

Abstract: This study compared levels of violence, social support, and post-traumatic stress between battered women charged with a violent crime against an abusive partner and those seeking help from a mental health clinic. Results indicated that forensic battered women were more likely than clinical battered women to report experiencing severe violence, including sexual abuse, in their relationships. Women in the forensic sample also reported less social support and greater post-traumatic stress than women in the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Psychological consequences of partner violence such as fear, anger, depression, and diminished self‐esteem are also positively linked to victim help seeking (Campbell, Miller, Cardwell, & Belknap, 1994; Kirkwood, 1993). The link between help seeking and social isolation and lack of social support that results from partner violence has also been examined among agency samples (see Dutton, Hohnecker, Halle, & Burghardt, 1994; Sullivan et al, 1992). Findings show that victims seek help from people they believe to be receptive (Bowker, 1983) and that perceived support and empathetic responses contribute positively to women’s coping (Waldrop & Resick, 2004).…”
Section: Research On Victim Help Seekingmentioning
confidence: 99%
“…Psychological consequences of partner violence such as fear, anger, depression, and diminished self‐esteem are also positively linked to victim help seeking (Campbell, Miller, Cardwell, & Belknap, 1994; Kirkwood, 1993). The link between help seeking and social isolation and lack of social support that results from partner violence has also been examined among agency samples (see Dutton, Hohnecker, Halle, & Burghardt, 1994; Sullivan et al, 1992). Findings show that victims seek help from people they believe to be receptive (Bowker, 1983) and that perceived support and empathetic responses contribute positively to women’s coping (Waldrop & Resick, 2004).…”
Section: Research On Victim Help Seekingmentioning
confidence: 99%
“…Studies of abused women who kill indicate that they often feel hopelessly trapped in a desperate situation from which they see no avenue of safe escape (e.g., Browne, 1987;Hamilton & Sutterfield, 1997;Totman, 1978). Compared with other battered women, battered women who kill are more likely to be unemployed (Goetting, 1995;Roberts, 1996), to have less social support (Dutton, Hohnecker, Halle, & Burghardt, 1994), to suffer more frequent assaults and receive more severe injuries (Browne, 1987;Gillespie, 1989), to be raped by their partners (Browne, 1987), to use less violence against their partners (O'Keefe, 1997), to be threatened with death by their partners, and to believe their lives are in danger (Browne, 1987;O'Keefe, 1997). The homicide occurs as part of an attempt to stop their partner from harming them or a child any further, to prevent an attack they believe to be imminent and life-threatening, or during a violent assault (Browne, 1986(Browne, , 1987Dugan, Nagin, & Rosenfeld, in press;Grant, 1995;Jurik & Winn, 1990;Maguigan, 1991).…”
Section: Motivesmentioning
confidence: 99%
“…A third body of research has focused on the relationship between PTSD and violence in battered women. Dutton et al () found that battered women who had attempted murder or had successfully murdered their abusive spouse had more severe PTSD than a clinical sample of battered women with PTSD who had not attempted murder. O'Keefe () compared battered women who killed their abusers and those incarcerated for other offenses and found that the battered women who had killed or seriously assaulted their batterers experienced more frequent and severe spousal abuse than those in the comparison group.…”
Section: Violence and Post‐traumatic Stress Disordermentioning
confidence: 99%